Rapid method for the quantification and identification of emerging compounds in wastewater based in nir spectroscopy and chemometrics - Quintelas, Cristina Maria Catalão (2019)
The typical methods to quantify emerging compounds in wastewater are time and reagent consuming and new methods for its quantification are welcome. This work describes the development and validation of a Fourier transform near-infrared (FT-NIR) spectroscopy methodology for the quantification of emerging compounds in wastewaters. For this purpose, 180 samples obtained from an activated sludge wastewater treatment process were analyzed in the range of 200 cm-1 to 14000 cm-1, and further treated by chemometric techniques to develop and validate the quantification models. The obtained results were found adequate for the prediction of atrazine, paracetamol, and desloratadine with coefficients of determination (R2) from 0.93 to 0.98 and residual prediction deviation (RPD) values above three, for the overall (training and validation) data points. These results are very promising and confirm that this technology can be seen as an alternative for the quantification of emerging compounds in wastewater.